A novel image-based high throughput screening assay discovers therapeutic candidates for adult polyglucosan body disease - Solmesky, L; Khazanov, N; Senderowitz, H; Wang, P; Minassian, B; Ferreira, I; Yue, W; Lossos, A; Weil, M; Kakhlon, O (Portland Press, 2017)
Glycogen storage disorders (GSDs) are caused by excessive accumulation of glycogen. Some GSDs (Adult Polyglucosan Body Disease (APBD), Tarui and Lafora diseases) are caused by intracellular accumulation of insoluble inclusions, called polyglucosan bodies (PB), which are chiefly composed of malconstructed glycogen. We developed an APBD patient skin fibroblast cell-based assay for PB identification, where the bodies are identified as amylase-resistant periodic acid-Schiff's (PAS) stained structures, and quantified. We screened the DIVERSet-CL 10,084 compound library using this assay in high throughput format and discovered 11 dose-dependent and 8 non dose-dependent PB-reducing hits. ~70% of the hits appear to act through reducing glycogen synthase (GS) activity which can elongate glycogen chains and presumably promote PB generation. Some of these GS inhibiting hits were also computationally predicted to be similar to drugs interacting with the GS activator protein phosphatase 1 (PP1). Our work paves the way to discovering medications for the treatment of PB-involving GSD, which are extremely severe or fatal disorders.